Fatores que influenciam o sucesso na prova de obtenção de título de especialista em infectologia: estudo retrospectivo -2011 A 2017 - REIS, M. R. (2018)
Background: Specialization is an important stage in medical training. In Brazil, a physician could obtain the specialist title by Medical Residency or specialist title test (STT) carried out by the specialty society. The specialty societies have autonomy to carry out the STT according to Brazilian Medical Association parameters. In addition to the Medical Residency, many societies allow graduates students from lato sensu courses recognized by them or physicians who prove a minimum time of specialty practice to take the test. Few studies have evaluated the factors associated with the approval on specialization tests in Brazil, thus justifying this study. Objective: To identify factors associated with the approval on Infectious diseases STT. Materials and methods: this was a retrospective study that included physicians who took the STT on infectious disease from 2011 to 2017. The sociodemographic and professional training data were collected through online questionnaire. Information on STT approval was taken directly from the Brazilian Society of Infectious Diseases database. The outcome was the STT approval and the main variable was participating on Infectious diseases Medical Residency program. The candidate's perception of the test was also evaluated. The institutional Ethics and Research Committee approved this project. Results: 185 physicians who had taken a STT between 2011 and 2017 and 62 agreed to participate. Due to the low representativeness of the volunteers from 2011 to 2016, only the 35 candidates who took the test in 2017 were considered for the analysis of factors associated with the STT approval. There was no statistically significant difference between STT approval and any analyzed variables, including Infectious Diseases Medical Residency. About 50% of candidates with Residence were not approved. Conclusion: none of the factors analyzed was associated with the STT approval. The failure index among candidates who had participated on the Infectious Diseases Residency program was higher than expected.